Modelo interno de risco de crédito de Basiléia II: possíveis impactos no capital mínimo exigido dos bancos - Yanaka, Guilherme M. (2009)
With the implementation of Basel II Accord in Brazil, the largest banks will be allowed to use the so-called IRB (Internal Ratings Based) model to compute the credit risk capital requirement. The aim of this thesis is to measure the difference between the minimum capital requirement (and, thus, in the capital ratio) calculated through the IRB approach and the one defined by the current regulation. Estimates of probabilities of default (PD) were made using transition matrices constructed from the Brazilian Central Bank Credit Register (SCR) data. The results show an increase in the capital requirement, contrary to what have happened in the G-10 countries.